A Quick Look Back at the Microalgal Biofuel Patents: Rise and Fall - Li, Dongzi; Du, Wei; Fu, Wantao; Cao, Xupeng (Frontiers in Bioengineering and Biotechnology, 2020)
Microalgae is a promising organism as the feedstock of the next generation biofuels, as well as high value nature products, such as astaxanthin, normally under certain stress cultivation conditions. With the clear industrialization targets, there have been two waves of microalgae R&D from the last century and showed obvious energy-driven trends. The overall R&D came into a valley now, however, the promising is still there. So here, from the industrialization point of view, the patent evolution concerning the microalgae for biofuels in the second wave were reviewed and summarized. These technology information will help the scientists to join together with industry to drive the next boost.